Radio-diagnosis of fecoliths and its non-surgical management in dogs - Khan, Arif; Gazi, Mohsin Ali; Dumralia, DM; Bagate, MS (Journal of Advanced Veterinary and Animal Research, 2014)
Two cases with a history of cessation of feces for 2 weeks, depression, lethargy and anorexia in two different dogs; a Labrador male and a Doberman female, were presented. On physical examination, abdominal distension along with intense pain was observed. Blood samples were collected from the dogs for hematological and biochemical analyses. The examination revealed an increased percentage of packed cell volume (PCV). By radiological examina-tion, radiopaque material was seen in the large intes-tinal tract. The condition was suggestive of fecolith. The cases were managed by means of non-surgical management. Through an 11-day long medicinal treatment, the dogs recovered uneventfully. DOI: http://dx.doi.org/10.5455/javar.v1i1p21-23 J. Adv. Vet. Anim. Res., 1(1): 21-23, March 2014